Rancang Bangun Platform Analisis Data Penjualan Dengan Menggunakan Algoritma Moving Average Study Kasus Heavy Cell: Studi Kasus Heavy Cell - Heryanto, Deni; Guntur nuriawan, Ridzky (Institut Teknologi Garut, 2025)
Heavy Cell is a telecommunications company facing two main issues: delays in procurement from suppliers and inefficient warehouse management. This study aims to develop a sales data analysis platform using the Moving Average Algorithm to improve stock management efficiency and demand forecasting. By applying the waterfall method, the research results in a web- and mobile-based platform expected to reduce procurement delays and optimize warehouse management. The contribution of this research lies in enhancing operational efficiency and customer satisfaction.